2011
DOI: 10.2967/jnumed.110.082032
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Ventricular Tachycardia Is Associated with Regional Myocardial Sympathetic Denervation Assessed with 123I-Metaiodobenzylguanidine in Chronic Chagas Cardiomyopathy

Abstract: Cardiac sympathetic denervation and ventricular arrhythmia are frequently observed in chronic Chagas cardiomyopathy (CCC). This study quantitatively evaluated the association between cardiac sympathetic denervation and sustained ventricular tachycardia (SVT) in patients with CCC. Methods: We prospectively investigated patients with CCC and left ventricular ejection fraction (LVEF) greater than 35% with SVT (SVT group: n 5 15; mean age 6 SD, 61 6 8 y; LVEF, 51% 6 8%) and patients without SVT (non-SVT group: n 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 23 publications
(37 reference statements)
1
54
1
12
Order By: Relevance
“…Cardiac 123 I-mIBG imaging is currently indicated for ''scintigraphic assessment of sympathetic innervation of the myocardium in patients with New York Heart Association [NYHA] class II or class III HF and left ventricular ejection fraction [LVEF] B35% … and to help identify patients with lower oneand two-year mortality risks, as indicated by an [HMR] ratio C1.6.'' Nevertheless, much literature suggests a potential broader use, 91 including identification of patients at increased risk of lethal cardiac arrhythmias in the setting of HF, [92][93][94][95] evaluating primary arrhythmic conditions, [96][97][98][99][100] assessing the presence and risk of ischemic heart disease, 101,102 including in situations of hibernating myocardium 103,104 and post-infarction, [105][106][107] evaluating pre-and post-cardiac transplant patients, [108][109][110] identifying diabetic patients at increased risk from cardiac autonomic dysfunction, 111,112 and monitoring toxicity from chemotherapy. 113 However, based on currently available literature, published guidelines, and the FDA package insert, the following indications can be recommended: 114 • For patients with NYHA class II or III heart failure with LVEF B35% to help stratify risk and to promote more informed clinical decision-making when the result of 123 I-mIBG study is likely to influence the decision regarding ICD implant.…”
Section: Tl-201mentioning
confidence: 99%
“…Cardiac 123 I-mIBG imaging is currently indicated for ''scintigraphic assessment of sympathetic innervation of the myocardium in patients with New York Heart Association [NYHA] class II or class III HF and left ventricular ejection fraction [LVEF] B35% … and to help identify patients with lower oneand two-year mortality risks, as indicated by an [HMR] ratio C1.6.'' Nevertheless, much literature suggests a potential broader use, 91 including identification of patients at increased risk of lethal cardiac arrhythmias in the setting of HF, [92][93][94][95] evaluating primary arrhythmic conditions, [96][97][98][99][100] assessing the presence and risk of ischemic heart disease, 101,102 including in situations of hibernating myocardium 103,104 and post-infarction, [105][106][107] evaluating pre-and post-cardiac transplant patients, [108][109][110] identifying diabetic patients at increased risk from cardiac autonomic dysfunction, 111,112 and monitoring toxicity from chemotherapy. 113 However, based on currently available literature, published guidelines, and the FDA package insert, the following indications can be recommended: 114 • For patients with NYHA class II or III heart failure with LVEF B35% to help stratify risk and to promote more informed clinical decision-making when the result of 123 I-mIBG study is likely to influence the decision regarding ICD implant.…”
Section: Tl-201mentioning
confidence: 99%
“…In this context, it is reasonable to hypothesise that in Chagas disease, the same pathophysiological mechanism may trigger arrhythmogenesis, considering the regional heterogeneity of the lesions in the intrinsic innervation 11,13,22,30 and in ventricular myocardium 64 of the chagasic heart. Indeed, an association between regional myocardial sympathetic denervation, detected by scintigraphy with 123 I-metaiodobenzylguanidine, and the occurrence of sustained ventricular tachycardia was observed in chagasic cardiomyopathy with preserved ventricular function 64 , and sympathetic modulation was noted to be affected in the ventricular myocardial also in chagasic subjects with the indeterminate form or borderline electrocardiogram 65 .…”
Section: Dysautonomic Arrhythmogenesis -A Working Hypothesismentioning
confidence: 99%
“…Indeed, an association between regional myocardial sympathetic denervation, detected by scintigraphy with 123 I-metaiodobenzylguanidine, and the occurrence of sustained ventricular tachycardia was observed in chagasic cardiomyopathy with preserved ventricular function 64 , and sympathetic modulation was noted to be affected in the ventricular myocardial also in chagasic subjects with the indeterminate form or borderline electrocardiogram 65 . In addition, cardiac sympathetic and cholinergic reinnervation was showed at least in experimental Chagas disease, and is likely that these phenomena occur in a regional heterogeneous manner resulting in unbalanced autonomic effect as a potential arrhythmogenic mechanism 66,67 .…”
Section: Dysautonomic Arrhythmogenesis -A Working Hypothesismentioning
confidence: 99%
“…Despite the well-established association between impaired autonomic cardiac modulation and sudden death in other clinical settings (13) , this association in ChD remains hypothetical. However, an association between sympathetic innervation defects (as detected by iodine-123 meta-iodobenzylguanidine scintigraphic studies) and sustained ventricular tachycardia (VT) has been demonstrated (14) , and autonomic-driven abnormal heart rate dynamics have been shown to precede ventricular tachycardia in ChD patients (14) .…”
Section: Pathogenesis and Pathophysiologymentioning
confidence: 99%